2013
DOI: 10.5943/mycosphere/4/2/6
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear reproductive cycle in the myxomycetes: a review

Abstract: Clark J, Haskins EF 2013 -The nuclear reproductive cycle in the myxomycetes: a review. Mycosphere 4(2), 233-248, Doi 10.5943/mycosphere/4/2/6Our understanding of the taxonomy, ecology and population biology of myxomycetes has been enhanced by investigations of the nuclear reproductive cycle of taxa in this group. These studies have involved light microscopy, electron microscopy, DNA cytophotometric reports and genetic investigations. Heterothallism with its associated life cycle events of syngamy and meiosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 87 publications
2
30
0
1
Order By: Relevance
“…In most modern eukaryotes, this handicap has been assuaged by the evolution of countless systems for identifying the opposite type via pheromones and mating behaviors, enhancing the efficiency of finding a mate, but options are still limited to half the population. In some lineages, the odds have been improved by the presence of multiple mating types-three or more in Dictyostelium (Bloomfield et al 2010(Bloomfield et al , 2011, seven in Tetrahymena (Phadke et al 2012;Cervantes et al 2013;Umen 2013), 13 in Physarum polycephalum (Collins and Tang 1977;Clark and Haskins 2010), and often thousands in the basidiomycetes (Raper 1966)-and in these cases more encounters are sexually fertile (.98% in some basidiomycetes). But more outcrossing is not always better, and in basidiomycete fungi there are multiple independent transitions from the tetrapolar outcrossing species with thousands of sexes back to bipolar species with just two mating types, where it has been suggested that different environments favor outcrossing versus inbreeding sexual cycles ).…”
Section: Multiple Mating Types and Homothallismmentioning
confidence: 99%
“…In most modern eukaryotes, this handicap has been assuaged by the evolution of countless systems for identifying the opposite type via pheromones and mating behaviors, enhancing the efficiency of finding a mate, but options are still limited to half the population. In some lineages, the odds have been improved by the presence of multiple mating types-three or more in Dictyostelium (Bloomfield et al 2010(Bloomfield et al , 2011, seven in Tetrahymena (Phadke et al 2012;Cervantes et al 2013;Umen 2013), 13 in Physarum polycephalum (Collins and Tang 1977;Clark and Haskins 2010), and often thousands in the basidiomycetes (Raper 1966)-and in these cases more encounters are sexually fertile (.98% in some basidiomycetes). But more outcrossing is not always better, and in basidiomycete fungi there are multiple independent transitions from the tetrapolar outcrossing species with thousands of sexes back to bipolar species with just two mating types, where it has been suggested that different environments favor outcrossing versus inbreeding sexual cycles ).…”
Section: Multiple Mating Types and Homothallismmentioning
confidence: 99%
“…Plasmodia are produced by the amoeboflagellate stage via the formation of a diploid zygotic cell by means of sexual fusion, or by the conversion of an apogamic diploid amoeboflagellate into a plasmodium (see reviews by Clark & Haskins [2010, 2013). In the sexual cycle amoeboflagellates differing at a multiple allelic mating system undergo syngamy after they have become competent upon reaching a critical cell density (Shipley & Holt 1982); while in the apogamic cycle, the amoeboflagellates are diploid, due to automixis (see Clark & Haskins 2013), and convert to plasmodia when they become competent.…”
Section: Plasmodiamentioning
confidence: 99%
“…In the sexual cycle amoeboflagellates differing at a multiple allelic mating system undergo syngamy after they have become competent upon reaching a critical cell density (Shipley & Holt 1982); while in the apogamic cycle, the amoeboflagellates are diploid, due to automixis (see Clark & Haskins 2013), and convert to plasmodia when they become competent. The zygotic or diploid amoeboflagellate cell apparently undergo a number of biochemical changes in their cell membrane (Ross & Shipley 1973) and a series of mitotic nuclear divisions without cell division to produce the multinucleate plasmodium.…”
Section: Plasmodiamentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the picture from these pioneering studies indicates that each morphospecies could be composed of an intricate pattern of core sexual strains, surrounded by a swarm of asexually reproducing clones that differ genetically and may differ in observable morphological traits (see [25] and references therein; [26]). …”
Section: Introductionmentioning
confidence: 99%